Data Security and Policy Management in E-Government Cloud Platforms: A Systematic Review of Challenges and Opportunities in Archipelagic Nations - Hasan, Mochammad Fuad (Universitas Komputer Indonesia, 2024)
The adoption of cloud computing in e-government offers significant scalability but presents unique architectural and regulatory complexities for archipelagic nations due to geographical fragmentation. This systematic literature review investigates the intersection of cloud data security, policy management, and topographical constraints. Following the PRISMA protocol, we analyzed 42 peer-reviewed articles (2019–2026) from Scopus, IEEE Xplore, and ScienceDirect. The findings reveal a critical